THE INTERPRETATION OF MESSAGE AND THE SOCIAL IMPACT OF SELECTION CONTRIBUTOR’S THREAD ON YOUNG ON TOP KASKUS COMMUNITY (YOTKC) - TARUNA, SAPTA INDRA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Critical Discourse Analysis, Interpretation of Message, and SocialImpact.This research aims to interpret the message in selection contributor’s thread on Young on Top Kaskus Community and analyze the social impact of the thread toward the kaskus users and hence tries to answer the problems of the study, i.e.: (1) what are the interpretation on the messages performed by Billy Boen on his motivational threads, (2) What are the textual interpretations performed by kaskusers on Billy Boen’s mot ivat ional threads, and (3) What are the social impact found on Billy Boen’s motivat ional threads.This research uses Critical Discourse Analysis theoretical framework from Norman Fairclough consisting of textual analysis, discursive practice, and sociocultural process. On the level of textual analysis, it has a purpose to interpret the message on Billy Boen motivational threads by using staging, perspectivization, and choices of word theories from Renkema. Discursive analysis is used to analyze the textual interpretations perfomed by kaskusers on his motivational threads. While social analysis is used to find out the impacts of his threads toward kaskusers. The writer used qualitative approach and document or content analysis method in conducting the research. The data were collected from kaskus especially from Billy Boen’s mot ivat ional threads and the comments posted by ISO kaskusers.The results indicate that (1) on staging analysis; Billy Boen’s utterances have already proved the theory of staging because most of his utterances use the same style of staging proposed by Renkema. In terms of perspectivization analysis, Billy Boen uses vision perspectivization rather than empathy perspectivization on his utterances, meanwhile on choices of words analysis, Billy Boen is balanced in using standard and non standard words on his utterances. (2) Most of ISO kaskus users basically can understand the messages on his motivational threads. (3) Most of ISO kaskusers are basically willing to do his advice and the number of ISO kaskuser who agrees with his opinion on his motivational thread are quite a lot.The writer suggests the next researchers to have good understanding on Critical Discourse Analysis especially how to relate between language, power, ideology and its social impact toward society. Then, the next researcher also needs to use the other theory than Critical Discourse Analysis theoretical framework proposed by Norman Fairchlough (1995).